PEMANFAATAN HIJAUAN PAKAN TERNAK Brachiaria Ruziziensis DAN Stylosanthes Guianenis MENDUKUNG USAHA TERNAK KAMBING DI KABUPATEN ASAHAN - Rusdiana, S.; Hutasoit, Rijanto (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
System maintenance goats in Indonesia, especially in the District High King of  the  North  Sumatra  regency  shavings  Proopinsi  done  the  traditional  way,  the availability of quality  feed is one of the limiting factors to determine the number of livestock kept by farmers. The purpose of this paper is to investigate the possibilities among  supplementary  feeding  is  applied  by  farmers  feed  ingredients  are  easily available at affordable prices, livestock forage planted palm perkebunana dilahan the age of 5 years with extensive 3 ha forage crops forage Brachiaria and Stylosanthes ruziziensis Guianeniserta, as well as waste agriculture, which can increase the rate of goats nuts. Livestock production performance shows R1, R2  and R3  highly significant (P <0.01) higher than R3, whereas to measure the growth rate of goats nuts (R1) which is  the  regression  coefficient  Yk  =  14:33  +2.02  X  (R2)  which  is  the  regression coefficient Yk = 14.34 +1.75 x, and (R3) which regress coefficient Yp = 14.34 + 1.58 y obtained regression equation with the same value of R2= 0.99, not only petambahan weight  are  visible  on  the  nut  goats  in  ruziziensis  give  forage  Brachiaria  and Stylosanthes  guianenis  but  goats  seem  nuts  over  fluffy,  slippery,  sparkling  eyes, smooth and healthy. Gains derived by farmers around R1 Rp.1.058.602/bulan B/C 1.2, R2  around  Rp.984.145/bulan  B/C  1.2  due  to  variable  expenses  and  the  cost  of production,  while  approximately  R3  Rp.666.268/bulan  B/C  1.1  expenditure concentrated on variable costs, labor costs and the purchase of seeds.